The importance of nutrition in aiding recovery from substance use disorders: A review - Jeynes, Kendall D.; Gibson, E. Leigh (Drug and alcohol dependence, 2017)
•Malnutrition is prevalent among individuals with alcohol and drug use disorders.•There is little nutritional advice for those recovering from substance use disorders.•Addiction and appetite share interacting brain and behavioural processes.•Malnutrition in substance use disorders may promote drug-seeking and impede recovery.•Effective treatments should incorporate nutritional assessment and therapy. Nutrition is a prerequisite for health; yet, there is no special nutritional assessment or guidance for drug and alcohol dependent individuals, despite the fact that their food consumption is often very limited, risking malnutrition. Further, the premise is examined that malnutrition may promote drug seeking and impede recovery from substance use disorders (SUD). A narrative review addressed the relationship between substance use disorders and nutrition, including evidence for malnutrition, as well as their impact on metabolism and appetite regulation. The implications of the biopsychology of addiction and appetite for understanding the role of nutrition in SUD were also considered. The literature overwhelmingly finds that subjects with alcohol use disorder (AUD) and drug use disorder (DUD) typically suffer from nutrient deficiencies. These nutrient deficiencies may be complicit in the alcoholic myopathy, osteopenia and osteoporosis, and mood disorders including anxiety and depression, observed in AUD and DUD. These same individuals have also been found to have altered body composition and altered hormonal metabolic regulators. Additionally, brain processes fundamental for survival are stimulated both by food, particularly sweet foods, and by substances of abuse, with evidence supporting confusion (addiction transfer) when recovering from SUD between cravings for a substance and craving for food. Poor nutritional status in AUD and DUD severely impacts their physical and psychological health, which may impede their ability to resist substances of abuse and recover their health. This review contributes to a better understanding of interventions that could best support individuals with substance use disorders.